In vitro antimicrobial activities of cinnamon bark oil, anethole, carvacrol, eugenol and guaiazulene against Mycoplasma hominis clinical isolates - Sleha, Radek; Mosio, Petra; Vydrzalova, Marketa; Jantovska, Alexandra; Bostikova, Vanda; Mazurova, Jaroslava (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2014)
AIMS: The aim of this study was to evaluate the antimicrobial effects of five natural substances against 50 clinical isolates of Mycoplasma hominis. METHODS AND RESULTS: The in vitro activity of selected natural compounds, cinnamon bark oil, anethole, carvacrol, eugenol and guaiazulene, was investigated against 50 M. hominis isolates cultivated from cervical swabs by the broth dilution method. All showed valuable antimicrobial activity against the tested isolates. Oil from the bark of Cinnamomum zeylanicum (MBC90 = 500 µg/mL) however was found to be the most effective. Carvacrol (MBC90 = 600 µg/mL) and eugenol (MBC90 = 1000 µg/mL) also possessed strong antimycoplasmal activity. CONCLUSIONS: The results indicate that cinnamon bark oil, carvacrol and eugenol have strong antimycoplasmal activity and the potential for use as antimicrobial agents in the treatment of mycoplasmal infections.
Keywords: azuleny; allylbenzenové deriváty; Allylbenzene Derivatives; Monoterpenes; Sesquiterpenes; cymeny; Microbial Sensitivity Tests; eugenol; Mycoplasma hominis; seskviterpeny guajanové; Eugenol; monoterpeny; Cymenes; anisoly; Oils, Volatile; oleje prchavé; seskviterpeny; mikrobiální testy citlivosti; Anisoles; Sesquiterpenes, Guaiane; Azulenes